Hedges and boosters in native and non-native library and information and computer science research articles - Fatemeh Mirzapour; Mohammad Rasekh Mahand (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2012)
The purpose of the present study is to compare and contrast the frequency of incidence of hedges and boosters used in Abstract, Introduction, and Conclusion sections of Library and Information (LI) and Computer Science (CS) research articles written by English native and non-native writers. Twenty research articles are selected from leading Iranian journals and international journals in two disciplines. The research articles are analyzed according to Holmes’ (1988) lexical devices classification, focusing on hedges and boosters. The analysis shows that the overall distribution of hedges and boosters in Library and Information articles is higher than Computer Science articles. Moreover, there are significant differences between native and non-native writers use of hedges and boosters.